Komunikasi Non Verbal Dalam Pemenangan Ajang Duta Genre Melalui Feed Instagram Di Bandarlampung - Adellia, Jihaan; Suryani, Eny Inti; Choiriyati, Sri (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research focuses on the importance of nonverbal communication in effectively conveying messages, particularly in the context of the GenRe Ambassador selection event. The study aims to investigate how participants' nonverbal communication can influence their success in the competition and its impact on the audience, especially Instagram users. The method used in this research is a qualitative approach with a case study involving data collection through interviews, observations, and documentation to understand participants' experiences and perceptions related to nonverbal communication. The research subjects are participants and committee members involved in the GenRe Ambassador selection in Bandarlampung. The results of the study indicate that body language, facial expressions, and vocal intonation play a crucial role in participants' success in engaging the audience and delivering messages. Challenges in interpreting nonverbal cues and managing content on social media platforms are also highlighted. Understanding and leveraging nonverbal communication are crucial for participants to excel in the GenRe Ambassador selection process and effectively disseminate educational messages on social media.